Pengembangan Media Pembelajaran Dengan Virtual Reality - Ramanda, Febri; Nur, Delyardi; Efriyandi, Yogi; Badriah, Siti Robi’atun (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2026)
Virtual Reality (VR)-based learning media is an innovative educational tool with significant potential to enhance the quality of learning. This study aims to support educators in utilizing immersive and interactive learning experiences to help students understand the material more effectively. The community service program focuses on providing teachers with knowledge, skills, and practical experience in developing and implementing VR-based learning media to improve teaching quality. The methods employed in this program include instructional sessions, demonstrations of VR technology in the learning process, as well as discussions and question-and-answer activities to deepen participants’ understanding of technology integration in schools. The expected outcomes of this initiative include enhanced teacher competence in utilizing VR technology, more engaging and interactive learning processes, and improved student comprehension of the material. This program reflects the commitment of the S1 Medical Informatics Study Program at Universitas Muhammadiyah Muara Bungo (UMMUBA) to contribute meaningfully to education, particularly through the application of information technology to support more effective and innovative.